HUBUNGAN BERAT BADAN DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMK N 6 PURWOREJO KABUPATEN PURWOREJO - Nur Sholichah; Larissa Ika Pramiswari (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
The menstrual cycle starts from the first day until the next menstruation comes. In SMKN 6 Purworejo students who are overweight and obese I affect the occurrence of menstrual cycle disorders. The purpose of this study was to determine the relationship between body weight and menstrual cycle in adolescent girls at SMKN 6 Purworejo. This research method uses observational analytic with cross sectional approach. The research population was 106 students at SMKN 6 Purworejo, with a simple random sampling of 84 students. Data collection techniques with checklists. The analysis of this study used the chi-square test with computerized SPSS Version 25.00 program. The results of this study indicate that the results of the significance of p (0.000) < (0.05), the conclusion is that there is a relationship between body weight and the menstrual cycle in adolescent girls at SMKN 6 Purworejo, so there is a relationship between body weight and menstrual cycles in adolescent girls at SMKN 6 Purworejo.